Rice CYP90D2 and CYP90D3 catalyze C-23 hydroxylation of brassinosteroids in vitro - Sakamoto, Tomoaki (Plant physiology and biochemistry : PPB, 2012)
Copyright © 2012 Elsevier Masson SAS. All rights reserved.